The effect of platinum-aluminide coating features on high-temperature fatigue life of nickel-based superalloy Rene®80 - Barjesteh M.M.; Zangeneh-Madar K.; Abbasi S.M.; Shirvani K. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Low cycle fatigue is the most important failure mode in Aviation/Industrial engine rotary turbine parts. In this paper, the influence of Pt-aluminide coating parameters on high temperature low cycle fatigue behavior of superalloy Rene®80 which is used to manufacture turbine blades, has been investigated. For this purpose, initial platinum layers of different thicknesses (2μm and 8μm) were coated on fatigue specimens. Then the aluminizing process was performed with two conditions of low temperature-high activity and high temperature-low activity. The results of microstructure investigations performed by scanning electron microscope and X-ray diffraction phase analysis indicated a three-layer structure for the coating (bi-phase (Ni,Pt)Al+PtAl2, single-phase (Ni,Pt)Al and interdiffusion zone) with different chemical compositions at both thicknesses of the platinum layer and using both aluminizing methods. Also, the results of low cycle fatigue tests at 871°C, R=0 and strain rate of 2×10 -3 s-1 showed a decline in fatigue properties in coated specimens as compared to uncoated sample, at total strains of 0.4, 0.8, and 1.2%. This reduction was lower in the low temperature-high activity with platinum layer thickness of 2μm, while it was more significant in the high temperature-low activity with the platinum layer thickness of 8μm. The fractography studies on coated and uncoated specimens indicated a mixed mode of ductile and brittle fracture.